Public relations plaza hotel semarang strategy: creating and maintaining a positive public image - Irawan, Joseph Aldo; Rahayu, Emik; Suryono, Chondro; Shabrina, Fitriatunnisa; Fitriyana, Dian (Surya Hijau Manfaat, 2024)
In the business world, having a good image is undoubtedly something that needs to be considered. This good image can be a way of income, especially for Plaza Hotel Semarang. Unfortunately, problems have arisen in the past and dragged on until now. This study aims to determine the public relations strategy to create and maintain a positive image of Plaza Hotel Semarang. The research method used to obtain quality data is through interviews and literature studies on related issues. The result is that Plaza Hotel Semarang has begun to design a new strategy to change its image among the wider community. However, some internal problems require special attention to be addressed first, especially in human resources. The researcher also listed several related inputs that are constructive and can be implemented appropriately for Plaza Hotel Semarang.